Improved Rhythm Pattern Reading Skills using the Eurythmics Dalcroze Method on Distance Learning for Junior High School - Sabila, Luthfia; Nandiyanto, Asep Bayu Dani; Kurniawan, Tedi; Bilad, Muhammad Roil (Universitas Pendidikan Indonesia (UPI), 2021)
Rhythm patterns are a regular flow of basic beats following several variations of melodic motion relating to the length of the short note and the lightweight of the accent (pressure) of the note. The study aimed to increase the knowledge of junior high school students in reading, writing, counting, and feeling the rhythm of a song using the Eurythmics Dalcroze learning method. The method used in this study is quantitative methods with data collection techniques. The result of this study is the Eurythmics Dalcroze method can increase students’ knowledge of rhythm patterns. The results showed an increase after students were given PowerPoint speakers and YouTube videos about rhythm patterns using the eurythmics Dalcroze method online through zoom with educators. Using the Dalcroze method, distance learning of rhythm patterns becomes easier to understand and becomes more enjoyable.